Havard Business Review's 10 Must Reads on Change Management - Harvard Business Review (Boston Harvard Business Review Press, 2011)
If you read nothing on change management, read these 10 articles. We have combined through hundreds of Harvard Business Review articles and selected the most important ones to help you spearhead change in your organization. This book will inspire you to: Lead change through eight critical stages Establish a sense of urgency Overcome addiction to the status quo Mobilize commitment Silence naysayers Minimize the pain of change Concentrate resources Motivate change when business is good
Includes index.
Keywords: Organizational change